EXPLORING THE MOST EFFECTIVE PLATFORM FOR PERSONAL BRANDING AMONG ORGANIZATIONAL STUDENTS - Asri Purba; Benedicta Eleanora Putri, Dwi Panggabean, Sandrina Amelia Angelica, Shinta Bella Simanjuntak (Adisam Publisher, 2025)
This study explores the most effective social media platforms for personal branding among students involved in campus organizations. The research aims to identify which platform— Instagram, LinkedIn, or others—is most influential in helping students establish their personal brand. The method used in this research involved distributing an online Google Forms survey to organizational students at several universities. The survey collected data on the social media habits of students, particularly focusing on which platforms they believe are most effective for showcasing their skills, achievements, and leadership roles. Results indicate that Instagram and LinkedIn are the most widely used platforms for personal branding, with Instagram being favored for its visual appeal and reach, while LinkedIn is preferred for its professional networking advantages. These findings highlight the importance of choosing the right platform depending on the branding goals and audience. Further studies could explore the impact of combining both platforms for a stronger personal brand.